Economic costs associated with moderate and late preterm birth: a prospective population‐based study. (22nd July 2015) - Khan, KA; Petrou, S; Dritsaki, M; Johnson, SJ; Manktelow, B; Draper, ES; Smith, LK; Seaton, SE; Marlow, N; Dorling, J; Field, DJ; Boyle, EM
<x xml:space="preserve">Abstract</x> Objective We sought to determine the economic costs associated with moderate and late preterm birth. Design An economic study was nested within a prospective cohort study. Sample Infants born between 32+0 and 36+6 weeks of gestation in the East Midlands of England. A sample of infants born at ≥37 weeks of gestation acted as controls. Methods Data on resource use, estimated from a National Health Service (NHS) and personal social services perspective, and separately from a societal perspective, were collected between birth and 24 months corrected age (or death), and valued in pounds sterling, at 2010–11 prices. Descriptive statistics and multivariable analyses were used to estimate the relationship between gestational age at birth and economic costs. Main outcome measures Cumulative resource use and economic costs over the first two years of life. Results Of all eligible births, 1146 (83%) preterm and 1258 (79%) term infants were recruited. Mean (standard error) total societal costs from birth to 24 months were £12 037 (£1114) and £5823 (£1232) for children born moderately preterm (32+0–33+6 weeks of gestation) and late preterm (34+0–36+6 weeks of gestation), respectively, compared with £2056 (£132) for children born at term. The mean societal cost difference between moderate and late preterm and term infants was £4657 (bootstrap 95% confidence interval, 95% CI £2513–6803; P < 0.001). Multivariable regressions revealed that, after controlling for clinical and sociodemographic characteristics, moderate and late preterm birth increased societal costs by £7583 (£874) and £1963 (£337), respectively, compared with birth at full term. Conclusions Moderate and late preterm birth is associated with significantly increased economic costs over the first 2 years of life. Our economic estimates can be used to inform budgetary and service planning by clinical decision‐makers, and economic evaluations of interventions aimed at preventing moderate and late preterm birth or alleviating its adverse consequences. Tweetable abstract Moderate and late preterm birth is associated with increased economic costs over the first 2 years of life.